A NEW CONCEPT FOR MUSEUM TRAINING IN GERMANY (Cadernos de Sociomuseologia, 2009)
To talk about a new concept for museum training seems perhaps, to be a little bit exaggerated. For long time you have all been talking about concepts and contents for museum training and as I figured out the debate on the topic in Germany is as old as the appearance of national museums in the 19th century. Men like Theodor Mommsen, Rudolph Virchow, Alfred Lichtwark, all well known historians and supporters of the museum idea, spoke and wrote not only about the importance of museums as cultural and educational institutions but also supported the idea of professionalisation of museums work. Some of the ideas of our ancestors are still part of an ongoing discussion. The topic of my talk today will be what king of personnel a museum of our time needs to cope with the growing demand for internal and external organization. I shall present to you a new training program for museum workers in Germany which aims not to produce a new group of researchers but to prepare students for the practical work in the museum field.